Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1980
DOI: 10.1085/jgp.76.3.381
|View full text |Cite
|
Sign up to set email alerts
|

Control of active proton transport in turtle urinary bladder by cell pH.

Abstract: The rate of active H § secretion (JH) across the luminal cell membrane of the turtle bladder decreases linearly with the chemical (ApH) or electrical potential gradient (A~) against which secretion occurs. To examine the control Of JH from the cell side of the pump, acid-base changes were imposed on the cellular compartment by increasing serosal [HCO~]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
2

Year Published

1983
1983
2007
2007

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 28 publications
4
14
2
Order By: Relevance
“…Thus, metabolic acidosis stimulated and metabolic alkalosis inhibited active proton secretion. Similar effects of serosal pH on proton secretion have been demonstrated in the rabbit PCT by Sasaki et al (28) and in the turtle bladder by Cohen and Steinmetz (29).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Thus, metabolic acidosis stimulated and metabolic alkalosis inhibited active proton secretion. Similar effects of serosal pH on proton secretion have been demonstrated in the rabbit PCT by Sasaki et al (28) and in the turtle bladder by Cohen and Steinmetz (29).…”
Section: Resultssupporting
confidence: 82%
“…It is, however, probable that the effects were mediated by changes in cell pH. Studies in the turtle bladder (29) and in tubular suspensions (30,31) have demonstrated that symmetrical pH changes in luminal and serosal fluid lead to cell pH changes in a similar direction. Previous studies in the turtle bladder demonstrated that isolated changes in luminal pH have only a small effect on cell pH (32), thus suggesting that cell pH varies with peritubular pH and may mediate the effect of peritubular pH on acidification.…”
Section: Resultsmentioning
confidence: 99%
“…This thesis, that peritubular alkalinity suppressed proximal hydrogen ion secretion, is consonant with observations of split droplet studies in the proximal tubule (4,21), of in vivo microperfusion studies (20) and in vitro microperfusion studies (22) using proximal tubules, as well as of studies using the turtle bladder (23). Thus, suppression of acidification by peritubular alkalinity may explain why reabsorptive saturation was observed in the proximal tubule as filtered bicarbonate concentration was simultaneously increased, and similarly why a reabsorptive plateau (a "Tm") has been observed in the whole kidney during bicarbonate titration studies (2).…”
Section: Resultssupporting
confidence: 71%
“…Bicarbonate absorption by both the turtle bladder and the CCT is electrogenic (6,11,(32)(33)(34)(35). Most data suggest that protons are electrogenically pumped into the lumen by an apical membrane proton translocating adenosine triphosphatase leaving OH-ions in the cell (35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Most data suggest that protons are electrogenically pumped into the lumen by an apical membrane proton translocating adenosine triphosphatase leaving OH-ions in the cell (35)(36)(37)(38)(39). Since HCO-absorption is inhibited by low CO2 tensions and acetazolamide (8,(32)(33)(34)36) it is likely that the intracellular OH-is carboxylated by C02, in a carbonic anhydrase facilitated step, to form HCO5, which then exits the cell. HCO-absorption is inhibited by the removal ofperitubular Cl-so it has been postulated that basolateral HCO-exit is mediated by a Cl-/HCO-exchanger (40, 41).…”
Section: Discussionmentioning
confidence: 99%